Partitioning behaviour of selected antibiotics in organic solvents - Mohd. Setapar, Siti Hamidah; Lau, S. W.; Yong, C.; Chen, P. L.; Shanjingm, Y.; Mat, Hanapi (Faculty of Chemical Engineering & Natural Resources, 2008)

(untitled)
The commercial production of antibiotics today uses the solvent extraction method in the extraction of antibiotics. Selection of solvent in any solvent extraction process is crucial due to technical and economic reasons. In order to get better understanding on the effect of solvent on the partitioning behaviour antibiotics, selected antibiotics such as kitasamycin, penicillin G, rifampicin and teicoplanin from aqueous buffer solution were studied using various groups of organic solvents such as alcohols, aldehydes, ketones, aliphatic hydrocarbons, kerosene and paraffin, as well as with addition of various extractants in kerosene system in order to enhance solute partitioning. The effects of solvent polarity, pH, antibiotic types and extractant addition on the partitioning behaviour of antibiotics were investigated. The polarity of solvents, in general, increases with an increase in solubility parameter and dielectric constant; and with a decrease in log P. Different groups of organic solvents exhibit different solvent polarity scales. Among them, alcohols are the most favourable solvent group for the partition of antibiotics, followed by aldehydes and ketones. Meanwhile antibiotic types such as kitasamycin and rifampicin displayed a very high degree of partitioning especially for solvent groups of alcohol, aldehyde and ketone over the pH range. On the other hand, addition of the extractant, TOMAC in kerosene displayed excellent partitioning efficiency for all the antibiotics used except kitasamycin whereas AOT was the next superb extractant in kerosene system for all except penicillin G.